WHAT DETERMINES THE TAX EVASION INTENTION OF TAXPAYERS? AN EMPIRICAL EVIDENCE FROM INDONESIA - Chayati, Nur; Triatmoko, Hanung; Ratih Wulandari, Trisninik; Sabilla Salim, Meka; Rizki Endiramurti, Saktiana (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This study examines how taxpayer egoism affects the relationship between tax evasion intention and its determinants. Tax evasion intentions are assessed both as a composite variable and a latent variable. This study evaluates the direct relationship between attitude, subjective norm, & perceived behavioral control on tax evasion intentions. Furthermore, this study used taxpayer egoism as a mediating variable. All variables used are in accordance with the perspective of the Theory of Planned Behavior. This research uses Ordinary Least Square (OLS) using SPSS and Partial Least Square using smartPLS to examine the mediation between the independent variable and the dependent variable. The results showed that taxpayer egoism has a positive effect on tax evasion intentions. This result is consistent with OLS Results that show the positive effect of taxpayer egoism on tax evasion intention. The direct effect of all seven determinants of tax evasion intention on tax evasion intention is statistically significant. Moreover, all seven factors that determine the intention to engage in tax evasion have a statistically significant effect on tax evasion intention through the phenomenon of taxpayer egoism.